Cytological Grading of Breast Tumors—The Human and Canine Perspective - Kuppusamy, Krithiga; Rajan, Aarathi; Warrier, Aarathy; Nadhan, Revathy; Patra, Dipyaman; Srinivas, Priya (Frontiers in Veterinary Science, 2019)
Human breast cancers (HBCs) are one of the leading causes of global cancer death among women. Domesticated canines are the most affected domestic species with a prevalence rate more than three times in women. While the human cancer patients receive substantial diagnostic and treatment facilities, inadequacy in canine cancer care, calls for greater attention. Fine Needle Aspiration Cytology (FNAC) is comparatively simple, quick and easily reproducible technique, which aids in pre-surgical diagnosis. In humans, FNAC has a standard protocol, the Robinson’s grading system, which has greater correlation with the established histological grading system of Scarff Bloom- Richardson. However, Canine Mammary Tumours (CMTs), which are known to be similar to HBCs in biological behaviour and gene expressions, still bank on the histopathological methods for diagnostic purposes. This review sheds light on various factors that could be considered for developing a standard FNAC technique for CMT grading and analyzes its future perspectives.